Pengaruh Pengungkapan Intellectual Capital, Reputasi Underwriter, Financial Leverage, Umur dan Size Perusahaan terhadap Underpricing Saham IPO di Bursa Efek Indonesia Periode 2014-2018 - Adinda Solida; Elvira Luthan; Nini Sofriyeni (Ekonomis: Journal of Economics and Business, 2020)
This study aims to examine and analyze the influence of factors that can influence underpricing during an IPO (Initial Public Offering) on the Indonesia Stock Exchange in the 2014-2018 period. This research uses quantitative research methods. The type of data used is secondary data, where the data collected is obtained through the official website of IDX, Yahoo Finance and the company's sample website. The population in this study were all IPO companies on the Stock Exchange in 2014-2018 and for the sample selection in this study using a purposive sampling method, as many as 77 sample companies were obtained. The analytical method used in this study is multiple linear regression. The results showed that intellectual capital disclosure had a negative and significant effect on the level of underpricing. While underwriter reputation, financial leverage, company age, and company size do not affect the level of underpricing.